2019
DOI: 10.3390/educsci9010040
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Turkish Pre-Service Teachers’ Perceptions and Views of Digital Literacy

Abstract: This study aims to investigate digital literacy perceptions of preservice teachers, and to identify quantity characteristics of first and second year preservice teachers’ digital literacy at a public university in Turkey. That is, pre-service teachers’ perceptions of digital literacy and their patterns of knowledge and use of digital literacy were measured within the scope of this study. Multiple sources of data, including a Likert scale and open-ended questions were collected to address the topic. Various sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
32
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 30 publications
(28 reference statements)
9
32
1
5
Order By: Relevance
“…Their good knowledge about the devices, applications, terminologies, and technical things related to digital technologies was caused by their high enthusiasm to digital technologies. It was proven by their high frequency in using internet, computer, multimedia and social ISSN: 2089-9823  Digital literacy scale of English pre-service teachers and their perceived readiness toward … (Khaira Liza) 77 networks in a week to read articles, news, and books.The result is in line with the study of Ata and Yildirim [52], in which they found pre-service teachers had high and positive perception about digital literacy. They articulated their enthusiasm in digital literacy by keeping update with innovation, processing information, using technological tools, finding, verifying and sharing information, using digital media effectively, using the internet effectively, writing and reading language programming, and using the technology in the right place and time.…”
Section: Total 5813supporting
confidence: 89%
“…Their good knowledge about the devices, applications, terminologies, and technical things related to digital technologies was caused by their high enthusiasm to digital technologies. It was proven by their high frequency in using internet, computer, multimedia and social ISSN: 2089-9823  Digital literacy scale of English pre-service teachers and their perceived readiness toward … (Khaira Liza) 77 networks in a week to read articles, news, and books.The result is in line with the study of Ata and Yildirim [52], in which they found pre-service teachers had high and positive perception about digital literacy. They articulated their enthusiasm in digital literacy by keeping update with innovation, processing information, using technological tools, finding, verifying and sharing information, using digital media effectively, using the internet effectively, writing and reading language programming, and using the technology in the right place and time.…”
Section: Total 5813supporting
confidence: 89%
“…Lack of understanding regarding the conception of digital literacy might limit preservice teachers' digital literacy development. The finding related to the basic conception of digital literacy is also in line with the study by Ata & Yildirim (2019) showing that despite pre-service teachers had high positive perceptions of digital literacy, they still encountered insufficient understanding of cognitive skills. Therefore, the projection of digital literacy education to pre-service teachers included in the curricula is necessary as they will be teacher in the future, and the use of technology is inevitable.…”
Section: The Conceptions Of Digital Literacy In Efl Academic Writingsupporting
confidence: 86%
“…( ), Yılmaz ve ark. (2015, Ata ve Yıldırım (2019) öğretmen adayları ile yapmış oldukları araştırmalarda, öğretmen adaylarının dijital okuryazarlık durumlarının iyi düzeyde olduğunu saptamıştır (Üstündağ ve ark., 2017;Yılmaz ve ark., 2015;Ata & Yıldırım, 2019). Öztürk (2021)'ün çalışmasında pandemi nedeniyle uzaktan eğitim sistemine geçişle birlikte öğretim elemanlarının dijital ortamda ders verme ve ders materyalleri hazırlama/kullanma konusunda kendilerini yetersiz hissettikleri belirlenmiştir.…”
Section: Discussionunclassified
“…Elçi ve Sarı (2016), öğrenciler ile yaptıkları çalışmada, cinsiyete göre dijital okuryazarlık düzeyi arasında anlamlı bir fark olmadığını belirlemiştir (Elçi & Sarı, 2015). Yontar (2019), Ata ve Yıldırım (2019) öğretmen adayları ile yürüttükleri çalışmalarında, kadınların dijital okuryazarlık yeterliliklerinin orta düzeyde, erkeklerin yüksek düzeyde olduğunu belirlemiştir (Yontar, 2019;Ata & Yıldırım, 2019). Kul (2020) öğrenciler ile yapmış olduğu çalışmada, kız öğrencilerin dijital okuryazarlıklarının daha yüksek olduğunu belirlemiştir (Kul, 2020).…”
Section: Discussionunclassified